Clinical and Some Risk Factors Associated with Theileria spp in Cows of Salah AL-Din Governorate, Iraq - Rafal Ali Hamad; Dr. Omaima Ibrahim Mahmoud; Dr. Maher Saber (Scholars Digest Publishing, 2023)
The current study aimed to diagnosis Theileria spp in cattle by using microscopic examination of blood smears , to record the clinical signs appearing on animals infection and to investigate the relationship between the infection and some risk factors such as sex ,age and presence of ticks on the animal. Fifty blood samples were collected during the period from September 2021 to the end of December 2022 from different areas in Salah Al-Din government (Al-Hamra, Albu Ajil, Baiji, AL-Alam ). The animals were suffering from one or more of clinical signs ( high temperature, lack of appetite, lethargy, pallor mucous membranes, superficial lymphadenopathy and tick infection) . The results showed that the total rate of infection was 40% . No significant differences between age groups, with 30% in animals that are less than a year and 16% 1-2 years and 10% in 2-3 years . and 4% in age 3< The study registered a significant difference according to gender, the rate of infection in male was 22 % and in females was 18% .
Keywords: Theileria parasite, Clinical signs, Risk factors, Epidemology, cows.